Nutritional and animal factors affecting nitrogen excretion in sheep and goats - Decandia M.; Atzori A.S.; Acciaro M.; Cabiddu A.; Giovanetti V.; Molina Alcaide E.; Carro M.D.; Ranilla M.J.; Molle G.; Cannas A. (Challenging strategies to promote the sheep and goat sector in the current global context, 2011)
The relationships between N excretion and diet in sheep and goats are reviewed. A database of 154 mean values concerning diet composition, nutrient intake and digestibility, faecal (FNE) and urinary (UNE) N excretion in sheep and goats at different physiological stages was developed. For each animal species and physiological stage, average and range values of live weight, fat-corrected milk, nutrient intakes, chemical composition of diets, crude protein (CP) apparent digestibility, FNE and UNE were calculated. Total N excretion (TNE) was calculated as the sum of FNE and UNE. Additionally a similar database for goats fed diets containing condensed tannins (CT) was developed and analysed. Values for UNE were higher (P<0.05) than those for FNE in each physiological stage examined both in sheep and goats. Lactating sheep showed higher (P<0.001) FNE (g/d per head) than lactating goats. Positive relationships were found between TNE, UNE (expressed as g/kg of dry matter (DM) intake) and dietary CP (percent DM) in sheep and goats for each physiological stage. Dry goats fed diets with low CP (mean ± S.E.: 10.8 ± 1.7 percent DM) and high condensed tannin levels (8.1 ± 1.9 percent DM) showed higher (P<0.05) FNE than UNE (mean ± S.E.: 8.0 ± 1.4 and 4.3 ± 1.4 g/d per head), in contrast with what usually found in animals fed free-tannin diets.
13. International Seminar of the Sub-Network on Nutrition of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2009/10/14-16, León (Spain)